Health Anxiety and Mental Health Outcome During COVID-19 Lockdown in Italy: The Mediating and Moderating Roles of Psychological Flexibility - Landi, Giulia; Pakenham, Kenneth I.; Boccolini, Giada; Grandi, Silvana; Tossani, Eliana (Frontiers in Psychology, 2020)
The COVID-19 emergency has severely affected the Italian population. During a pandemic, those with high health anxiety are at risk of adverse mental health outcomes, including peritraumatic distress and mood disturbance. No prior research has explored the role of psychological flexibility in protecting people at high risk of poorer mental health impacts due to health anxiety during a pandemic. Psychological flexibility is the cornerstone of psychological health and resiliency. It involves behaving consistently with one’s chosen values even in the presence of emotional and mental discomfort. This study examined the mediating and moderating roles of psychological flexibility in the link between trait health anxiety and three mental health outcomes: COVID-19 peritraumatic distress, anxiety and depression. We hypothesized that higher psychological flexibility would decrease the negative impacts of trait health anxiety on mental health outcomes. During the mandatory national lockdown (M = 35.70 days, SD = 8.41), 944 Italian adults (75.5% female, M = 38.86 years, SD = 13.20) completed an online survey consisting of standardized measures of psychological flexibility, health anxiety, COVID-19 distress, anxiety and depression. Results indicated that psychological flexibility did not moderate the link between health anxiety and mental health outcomes. Rather, greater psychological flexibility mediated decreases in the adverse effects of trait health anxiety on COVID-19 distress, anxiety and depression. In particular, two psychological flexibility processes, observing unhelpful thoughts rather than taking them literally (defusion) and values-based action (committed action), mediated decreases in the negative effects of health anxiety on all mental health outcomes. In contrast, the psychological flexibility process acceptance, which involves openness to inner discomfort, mediated increases in negative mental health outcomes. Overall, the combination of these processes mitigated the detrimental impacts of trait health anxiety on mental health during the emergency mandatory COVID-19 nationwide lockdown. Findings suggest embracing (rather than avoiding) inner discomfort and observing associated unhelpful thoughts, while also engaging in values-based action, increase resilience during adversity. Evidenced-based large-scale online public health interventions that target psychological flexibility in those experiencing health anxiety in the context of a pandemic are urgently needed. Many empirically-based ACT interventions are suited for this purpose.